2010
DOI: 10.1111/j.1365-313x.2009.04054.x
|View full text |Cite
|
Sign up to set email alerts
|

PYR/PYL/RCAR family members are majorin‐vivoABI1 protein phosphatase 2C‐interacting proteins in Arabidopsis

Abstract: Abscisic acid (ABA) mediates resistance to abiotic stress and controls developmental processes in plants. The group-A PP2Cs, of which ABI1 is the prototypical member, are protein phosphatases that play critical roles as negative regulators very early in ABA signal transduction. Because redundancy is thought to limit the genetic dissection of early ABA signalling, to identify redundant and early ABA signalling proteins, we pursued a proteomics approach. We generated YFP-tagged ABI1 Arabidopsis expression lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
374
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(394 citation statements)
references
References 67 publications
14
374
1
5
Order By: Relevance
“…A model presented in recent reports highlighted the role of the ABA receptor(s) in direct regulation of group A PP2Cs (Ma et al, 2009;Park et al, 2009). In this model, the receptor binds and inhibits ABI1 and ABI2 in the presence of ABA, which leads to activation of SnRKs and downstream signaling molecules (Park et al, 2009;Nishimura et al, 2010). Whether or not similar ABA receptor molecule(s) bind to PP2Cs in mosses or liverworts is not clear.…”
Section: Mpabi1 Serves As a Negative Regulator Of Aba Signalingmentioning
confidence: 99%
“…A model presented in recent reports highlighted the role of the ABA receptor(s) in direct regulation of group A PP2Cs (Ma et al, 2009;Park et al, 2009). In this model, the receptor binds and inhibits ABI1 and ABI2 in the presence of ABA, which leads to activation of SnRKs and downstream signaling molecules (Park et al, 2009;Nishimura et al, 2010). Whether or not similar ABA receptor molecule(s) bind to PP2Cs in mosses or liverworts is not clear.…”
Section: Mpabi1 Serves As a Negative Regulator Of Aba Signalingmentioning
confidence: 99%
“…Although previous studies suggested that many are ABA receptors and have redundancy [2,31], they also showed functional differences [6,27]. In the presence of ABA, PYR1 and PYLs 1-12 reduced the activity of ABI1 and activated SnRK2.6 to induce RD29B-LUC expression in Arabidopsis mesophyll protoplasts [4].…”
Section: Pyl13 Differs From the Other Pyls And Does Not Function As Amentioning
confidence: 99%
“…Although the PYL family proteins have been studied intensively in recent years [6,[28][29][30][31], little information is available for PYL13, which differs from other PYLs in the highly conserved regions of their ABA-binding pocket. To study the function of PYL13, we examined the interaction of PYL13 with clade A PP2Cs and the effects of PYL13 on the PP2Cs both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a chemical genetic approach using a synthetic selective ABA agonist, pyrabactin, made it possible to identify a family of soluble ABA receptors, named PYR/PYL/RCAR for PYRABACTIN RESISTANCE1/PYR1-LIKE/ REGULATORY COMPONENTS OF ABA RECEPTORS, respectively [8,9]. In a convergent approach, yeast-two hybrid screenings [9,10] and in planta interaction studies [11] identified these receptors through their capacity to bind to phosphatases type-2C (PP2Cs), which are key negative regulatory components of the pathway involved in the dephosphorylation of certain sucrose non-fermenting 1-related subfamily 2 (SnRK2) kinases [12,13,14].…”
Section: Introductionmentioning
confidence: 99%